ChemInform Abstract: Catalytic Asymmetric Addition of Meldrum′s Acid, Malononitrile, and 1, 3‐Dicarbonyls to ortho‐Quinone Methides Generated in situ under Basic Conditions. Issue 35 (September 2015) - Caruana, Lorenzo; Mondatori, Martina; Corti, Vasco; Morales, Sara; Mazzanti, Andrea; Fochi, Mariafrancesca; Bernardi, Luca
Abstract A new approach to the utilization of highly reactive and unstable ortho‐quinone methides (o‐QM) in catalytic asymmetric settings is presented.